Targeting the BAG2/CHIP axis promotes gastric cancer apoptosis by blocking apoptosome assembly - Liu, Qian; Chen, Qingjie; Wei, Hong; Tang, Baoyuan; Tian, Binbin; Ma, Zhijian; Gu, Qianlin; Su, Xiaolu; Dong, Yuman; Shi, Wengui; Luo, Changjiang (Frontiers in Immunology, 2025)
Apoptosis has been shown to play an important role in the treatment of gastric cancer, and BCL2-associated athanogene 2(BAG2) has been found to be able to inhibit apoptosis by interacting with multiple apoptosis regulators. In this study, we demonstrate that BAG2 functions as an independent prognostic factor, correlating with unfavorable clinical outcomes in patients with gastric cancer (GC). We demonstrate that BAG2 upregulation inhibited apoptosis and increased proliferation, migration, and invasion of GC cells, whereas the opposite results were obtained in BAG2-deficient GC cells. Mechanistically, BAG2 interacts with the c-terminus of HSP70-interacting protein(CHIP) to inhibit the ubiquitination degradation of Heat shock protein70(HSP70) and increase the binding of HSP70 to apoptotic protease-activating factor 1(Apaf1). The reduced ubiquitination degradation of HSP70 reduces the release of mitochondrial cytochrome C (Cytc), which ultimately inhibits the formation of apoptotic bodies assembled by Cytc and Apaf1. The above effects of BAG2 inhibit the formation of Cytc and Apaf1-assembled apoptotic bodies. Furthermore, we screened FIIN-2, an inhibitor of the BAG2 complex, which effectively halts the malignant development of GC triggered by reduced apoptosis by blocking BAG-CHIP binding. In conclusion, this study highlights BAG2’s key role in regulating apoptosis and confirms FIIN-2’s effectiveness in GC-targeted therapy.